Cationic Trialkylphosphates: Synthesis and Transfection Efficacies Compared to Phosphoramidate Analogues (Eur. J. Org. Chem. 36/2014). Issue 36 (December 2014) - Le Corre, Stéphanie S.; Berchel, Mathieu; Le Gall, Tony; Haelters, Jean‐Pierre; Lehn, Pierre; Montier, Tristan; Jaffrès, Paul‐Alain
Abstract : The cover picture shows, in an illustrative manner, the two‐step sequence that produces cationic trialkylphosphates incorporating two different lipid chains. A novel family of cationic lipids is reported, which is characterized by a trimethylammonium head group linked, via a phosphate function, to either two identical or two different lipid chains. The ability of these new vectors to deliver a reporter (luciferase‐encoding) plasmid DNA into human‐derived cell lines was evaluated. Comparisons with equivalent lipophosphoramidates were made. Details are discussed in the article by P.‐A. Jaffrès et al. on8041 ff .